A Million Veteran Program GWAS of Alzheimer's Disease and Related Dementias in African Americans Identifies Multiple Genome‐Wide Significant Dementia Risk Loci. (20th December 2022) - Sherva, Richard; Zhang, Rui; Farrer, Lindsay A.; Sahelijo, Nathan; Jun, Gyungah R; Anglin, Tori; Chanfreau, Catherine; Cho, Kelly; Fonda, Jennifer; Gaziano, J. Michael; Harrington, Kelly; Ho, Yuk‐Lam; et al.
Abstract: Background: While genome wide association studies (GWASs) of Alzheimer's Disease (AD) in European ancestry cohorts (EUR) have identified >70 potentially independent AD risk loci, progress in non‐European populations has lagged. In this study, data from US Veterans of African ancestry (AFR) from the Million Veteran Program (MVP) biorepository were used to identify genetic factors associated with AD and related dementias (ADRD). Method: Using the VA electronic medical record, 4, 012 AFR ADRD cases (algorithm includes codes for AD and dementias such as vascular dementia) and 18, 435 dementia‐free AFR controls were identified for inclusion in the GWAS. A GWAS was also performed using proxy dementia based on survey‐reported AFR participant parental history of AD or other dementia that included 4, 385 maternal cases, 2, 256 paternal cases, and 45, 970 controls. Meta‐analysis of the case control and proxy results for was performed and then subsequently combined with results from a AFR AD GWAS conducted by the Alzheimer Disease Genetics Consortium (ADGC; Kunkle et al., 2021). Result: The AFR MVP GWAS (case‐control + proxy) yielded genome‐wide significant associations with several loci including APOE (p=2.48x10 ‐101 ), ROBO1 (rs11919682, p=1.63x10 ‐8 ), and RP11‐340A13.2 (rs148433063, p=8.56x10 ‐9 . The ROBO1 and RP11‐240A13.2 SNPs were not replicated in the ADGC sample (missing or not significant). The meta‐analysis of MVP and ADGC GWAS results (Table 1) additionally identified genome significant SNPs near known AD risk genes TREM2 (rs73427293, p=2.95x10 ‐9 ), CD2AP (rs7738720, p=1.14x10 ‐9 ), and ABCA7 (rs73505251, p=3.26x10 ‐10 ). Comparison of expression of genes near variants with suggestive evidence of association (p<5x10 ‐7 ) in the brains of EUR AD cases and controls from Framingham Heart Study, Religious Orders Study/Rush Memory and Aging Project, Mayo‐Mount Sinai Brain Bank, and Boston University Brain Bank (Panitch et al.) identified several differentially expressed genes including EML6 . Conclusion: The AFR dementia GWAS presented here is the largest to date. It increased the number of genome wide significant common‐variant dementia loci reported in AFR cohorts from two to six, including genes previously implicated in EUR cohorts. Increasing representation of AFRs is an important priority in genetic studies and may lead to increased insight into AD pathophysiology and reduce health disparities.